Psychological distress and associated personal and workplace stressors among breast cancer survivors - Yong, Heng Weay (2012)
The number of women employed at the time of breast cancer diagnosis has risen gradually and most of the survivors were younger than 65 years and the majority would most likely return to work. Working survivors might face social and economic hardship, workplace stress and psychological burdens either individually or with their coworkers or their superiors. Thus, this study will promote a better understanding of the psychological distress experienced by working breast cancer survivors, and to determine associated workplace and personal factors contributing to the psychological distress. Objective: To determine personal and workplace stressors and their associations with psychological distress of working breast cancer survivors. Methodology: This cross-sectional study was conducted at 2 hospitals and 4 support groups. One hundred and fifty breast cancer survivors were recruited. Personal Stress Inventory (PSI) and Job Content Questionnaire (JCQ) were used to determine personal and workplace stressors, respectively. Psychological distress was determined using the Hospital Anxiety and Depression Scale (HADS) and Distress Thermometer (DT). Salivary a-amylase assay kit was used to analyze the salivary a-amylase levels, are indicator of psychological distress. Results: The Cronbach's alpha coefficient for the Malay translated version of HADS subscales were better (a = 0.81 for anxiety and a= 0.73 for depression) compared to the Chinese version (a = 0.67 for anxiety and a= 0.70 for depression). The cut-off point of 5 on DT had maximized the balance between sensitivity and specificity rates in detecting the caseness of anxiety, depression and distress. In personal, family and household stressors were significantly associated with anxiety (OR =1.42, p<O.OOl), depression (OR =1.18, p<O.OOl) and distress on both HADS (OR =1.24, p<O.OOl) and DT (OR =1.20, p<O.OOl). For workplace stressors, only job strain was significantly association with anxiety (OR=4.74, p<O.OOl). Psychological job demand was significantly associated with depression (OR =8.08, p<O.OOl) and social support was a protective factor for depression (OR =0.39, p=0.041). Psychological job demand and job strain showed significant associations with distress on both HADS (OR =4.40, p=0.012; OR=6.09, p=0.032) and DT (OR =5.49, p=0.052; OR =3.17, p=0.037). For stress-related symptoms, musculoskeletal system related symptoms (OR =4.21, p=0.003) and sleeping habit and pattern problem (OR =5.24, p=0.002) showed significant association with anxiety. While, work load and task delivery problem is the only stress¬related symptom that showed significant association with depression (OR =3.45, p=0.030). Memory and attention span problem (OR =5.42, p=0.037) and work load and task delivery problem (OR =4.38, p=0.008) showed significant association with distress HADS while musculoskeletal system related symptoms (OR =4.63, p=O.Oll) and rk load and task delivery problem (OR =8.03, p=0.007) showed significant association h distress on DT. Salivary a-amylase showed significant association with anxiety (OR 21, p=0.032), depression (OR =7.78, p=0.002) and distress on HADS (OR =6.48, l.002). Therefore, salivary a-amylase was found to be a potential indicator of chological distress. Conclusion: The Malay and Chinese version of HADS and DT 'e reliable and validated measures. It is clear that most distressed survivors ,experienced anxiety, depression and distress due to both workplace and personal factors. Among all stressors, psychological job demand, job strain and family and household factors, symptoms of musculoskeletal system, sleeping habit and pattern problem, memory and attention span problem and work load and task delivery problem were significant predictors of psychological distress whereas social support served as a protective factor. The salivary a-amylase level was a reliable indicator of psychological distress.